EFFECTIVENESS OF HANDWASHING PRACTICE DEMONSTRATION IN CHILDREN AGED 7-9 YEARS AS A PREVENTIVE EFFORT OF DIARRHEA OCCURRENCE AT SON SIDOTENTREM II BANGILAN DISTRICT TUBAN REGENEY IN 2017 - Mulyani, Sri (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2019)
ABSTRACT Health  education  is  an  effort  or  activity  to  create  behavior  of  society which  is conducive  to health. Less clean hand wash in children is one factor that can cause diarrhea. The purpose  of this study is to know the effectiveness of handwashing practice  demonstration in children aged  7-9 years  as a preventive  effortof diarrhea occurrence  at SDN Sidotentrem II Bangilan District Regeney  Tuban in 2017.The type of research used is experimental  research, research design using quasi pra eksperimen (pre-post   test  design). The population is all children aged 7-9 years, 140 children, and the number of samples  are 140 respondents  who meet the inclusion criteria by using non probability sampling with  saturated   sampling   technique. Methods   of  data collection with handwashing  demonstration questionnaire which then in editing, coding, scoring and tabulating, are presented in the estimation and percentage curve tables.The result  of the research  showed  that from   /40  respondents  before getting handwashing demonstration, the  majority was not correct in hand washing  as  many  as  140 respondents (100%). respondents  after hand  washing  demonstration  from   140 respondents more than partially  true in hand washing practice  as many as 94 respondents  (67./%)  and less than partially  incorrect in hand washing practice as many as 46 respondents  (32.9%).In  conclusion  effective  handwashing  demonstration   in children  aged  7-9 years  as apreventive  effort incident diarrhea  in SDN Sidotentrem  II District  Bangilan Tuban Regeney. The results of this study are expected  to add knowledge  and skills  to the respondents  about the practice of hand washing correctly. Keywords: Handwashing  Practice,  Demonstration.